2014
DOI: 10.1111/ics.12166
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory and anti‐bacterial properties of tetramethylhexadecenyl succinyl cysteine (TSC): a skin‐protecting cosmetic functional ingredient

Abstract: Tetramethylhexadecenyl succinyl cysteine represents a novel cosmetic functional ingredient that provides a dual modulating benefit of skin protection to individuals by reducing inflammation in keratinocytes, endothelial and mononuclear cell types and S. pyogenes counts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…1a) in which a glutamine is thioacetylated to the cysteine residue possesses anti-inflammatory properties by inhibiting UV-induced pro-inflammatory mediators in human keratinocytes, similar to previous IPC compounds [15, 16]. Furthermore, we demonstrate for the first time that SIG-1191 upregulates AQP3 gene expression in monolayer keratinocytes and both gene expression and protein production in reconstructed three-dimensional human skin cultured at the air–liquid interface.…”
Section: Introductionsupporting
confidence: 80%
“…1a) in which a glutamine is thioacetylated to the cysteine residue possesses anti-inflammatory properties by inhibiting UV-induced pro-inflammatory mediators in human keratinocytes, similar to previous IPC compounds [15, 16]. Furthermore, we demonstrate for the first time that SIG-1191 upregulates AQP3 gene expression in monolayer keratinocytes and both gene expression and protein production in reconstructed three-dimensional human skin cultured at the air–liquid interface.…”
Section: Introductionsupporting
confidence: 80%
“…Isoprenylcysteine (IPC) small molecules have been identified as a novel class of topical anti‐inflammatory and antimicrobial cosmetic functional ingredients (CFI) . IPCs have been shown to inhibit signaling activation in the membrane, by competing with isoprenoid groups for prenyl‐binding sites on membrane‐associated proteins .…”
Section: Introductionmentioning
confidence: 99%
“…SIG1273 (tetramethylhexadecenyl succinyl cysteine) is a second generation IPC CFI with anti‐inflammatory activity and was the first reported IPC to also have antimicrobial properties . SIG1273 has a broad range of anti‐inflammatory activities, abrogating toll‐like receptor 2 (TLR2), toll‐like receptor 4 (TLR4), and T‐cell receptor (TCR) signaling .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported that IPC compounds inhibited TLR2‐ and TLR4‐induced pro‐inflammatory cytokine production of IL‐6 and IL‐8 and possessed antibacterial activity . As demonstrated here, subsequent medicinal chemistry efforts yielded a novel phytyl IPC, SIG1459 (Tetramethyl‐hexadecenyl‐cysteine‐formylprolinate) with antibacterial activity against the gram‐positive organism, including eradicating biofilm formation and inhibiting TLR2‐induced inflammation (Table and ).…”
Section: Discussionmentioning
confidence: 56%